Combination of Vitamin D and Vitamin E Against Bacterial Infections - Bangun, Primta; Rusip, Gusbakti; Mutia, Maya Sari (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Bacterial infections are a significant health problem worldwide, caused by various microorganisms that can infect different parts of the human body. Bacteria are single-celled microorganisms that can be found in various environments, including in the human body, and most of them are harmless. However, some species of bacteria can cause serious infections and inflammation that require proper medical attention. Some examples of bacteria that cause infections include Streptococcus pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, Vibrio cholerae, Mycobacterium tuberculosis, Escherichia coli, and Staphylococcus aureus. A sufficient vitamin D level in the body can enhance antimicrobial activity against various pathogens, including bacteria, viruses, and fungi. Vitamin E is known to be a powerful antioxidant and has a positive effect on the immune system. It plays a role in protecting immune cells from oxidative damage and enhancing the immune response to infection. The combination of vitamins D and E offers significant potential in the prevention and management of bacterial infections, as both contribute to improved immunological function through different and complementary mechanisms.